PENGARUH REGULASI DIRI DAN SIKAP PADA MATEMATIKA TERHADAP KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA - ELFIADI, ELFIADI (Jurnal Pendidikan Usia Dini, 2016)
Mathematics is a part of cognitive development that need to optimalize towards earlychildhood students. Mathematics can help the children to think logic, sistematic, and solve theproblems in the daily life. Unfortunately, from the research in some of elementary school at KotaJuang Bireuen sub district has found that student’s ability to solve about mathematics problem stilllow especially for third grade students. The purpose ofthis study is to know the direct effects ofselfregulation and mathematics attitude towards student’s ability to solve mathematics problems. Thisresearch use quantitatif asosiatif approach. The method of this research use path analysis survey.In this research there are 95 students from 4 schools that chosen by multistage random samplingtechnique. Data collection with test and questionairre. The results of the research show that thereare positive direct effect of self regulation towards mathematics problem solving ability with score0.321. There are positive direct effect ofmathematics attitude towards mathematics problem solvingwith score 0.384, and there are positive direct effect of self regulation toward mathematics attitudewith score 0.324.The conclusion of this research are : (1) self regulation give direct positive effecttowards mathematic problem solving ability, (2) mathematics attitude give positive direct effecttowards mathematics problem solving ability, (3) self regulation give positive direct effect towardsmathematics attitude.